Reproductive and economic performance of local livestock in southwestern Madagascar: Potentials and constraints of a highly extensive system. (November 2016) - Feldt, Tobias; Neudert, Regina; Fust, Pascal; Schlecht, Eva
Abstract: In the dry Mahafaly region of southwestern Madagascar, livestock keeping plays a key role in people's livelihoods. Especially zebu cattle and goats are socially important and contribute considerably to regular income of local households. We therefore analyzed the reproductive performance of local breeds along with livestock owners' culling strategies to determine herd dynamics, opportunities for economic development, as well as potential improvements, by using a combined methodical, both production-oriented and economic approach. Data was collected through interviews on the progeny history of breeding females (506 cows and 593 does) and their offspring (721 calves and 1073 kids). Based on the results, reproduction parameters were calculated and entered into the PRY Herd Life model to simulate herd development for present management ( status quo ) and two alternate scenarios assuming either (i) improved feeding and resulting higher productivity of breeding females or (ii) improved culling. Based on prices collected at local markets, a Monte Carlo simulation was used to estimate annual costs and revenues from livestock keeping. Age at first parturition was 40.5 ± 11.2 months for cattle and 21.3 ± 9.8 months for goats. Females from both species showed long parturition intervals (cattle 24.2 ± 8.7 months, goats 12.4 ± 5.7 months) whereas reported offspring mortality was low with 2.5% of cattle and 18.8% of goats dying before reaching maturity. On the other hand, market prices, especially for zebus, were quite high, leading to annual contribution margins of 33 € per cattle unit and 11 € per goat unit. The simulations indicated that improved feeding could support substantial herd expansion and productive offtake rates, whereas improved culling would stabilize livestock numbers and concomitantly increase monetary herd output. Even though the current livestock husbandry system appears profitable, it might reach its limits in the near future due to the region's restricted ecological carrying capacity. Increasing livestock offtake would allow livestock keepers to raise their economic benefit without compromising herd development or enhancing the pressure on pasture resources. Highlights: Analysis of reproductive performance and economic potential of Malagasy zebu cattle and goats Cows and does show late age at first parturition and long parturition intervals. Annual contribution margins of 33 € per cattle and 11 € per goat unit. Simulation of two alternate scenarios assuming improved feeding and culling. Scenario modelling shows considerable production potential if based on improved herd management.